2017
DOI: 10.3390/en10121964
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Diagnosis of Performances in Photovoltaic Systems: A Case Study in Southern Spain

Abstract: Abstract:The starting point of the operation and maintenance tasks in photovoltaic plants is the continuous monitoring and supervision of its components. The great amount of registered data requires a major improvement in the ways this information is processed and analyzed to rapidly detect any potential fault, without incurring additional costs. In this paper, a procedure to perform a detailed graphical supported analysis of the operation of photovoltaic installations, based on inverter data, and using a self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…This study does not take into account effects such as shading as the aim of the paper is to visualize performance rather than detect reasons behind over-or underperformance [16]. The PR was calculated using Equation (1), where Y f is the final system yield and Y r is the reference yield [15]. Since high-resolution, up-to-date annual irradiation data was not available for the rest of the countries, PR was calculated only for The Netherlands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study does not take into account effects such as shading as the aim of the paper is to visualize performance rather than detect reasons behind over-or underperformance [16]. The PR was calculated using Equation (1), where Y f is the final system yield and Y r is the reference yield [15]. Since high-resolution, up-to-date annual irradiation data was not available for the rest of the countries, PR was calculated only for The Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…Several countries have utilized this potential to create a competitive market in view of a green energy future, which led to an increase in small and medium-sized residential solar PV installations [1,2]. These small-sized installations (with capacities less than 10 kWp) are scattered and operate under diverse conditions without adequate monitoring equipment.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the elements identified in the reading of the materials were aligned around four Fundamental Viewpoints (FVs): (1) Strategic alliances: evaluate the level of interaction of the Solar Power Plants with the other stakeholders; (2) Management and Strategic Processes: measure the performance of plant's internal operations; (3) Innovation in Photovoltaic Power Generation: Evaluate the performance of the plants as innovative organizations, mastering the technology used as well as prospecting for future scenarios; and (4) Monitoring of Photovoltaic Generation: Measure the state of conservation of installed system as well as monitoring economic and financial oscillations which are relevant to PV energy sector. The performance indicators used to quantify the technical monitoring points of Photovoltaic Generation were based on the software S·lar2 [27].…”
Section: Construction Of Modeling For Competitiveness Measurementmentioning
confidence: 99%
“…Thus, it can be seen that PV energy generation is embedded in a globally competitive environment, a characteristic that forces PV power plants to perform most processes relevant for its competitiveness with maximum efficiency. According to a research carried out in Cordoba, Spain [27], improving the profitability of photovoltaic installations requires optimizing their production, thus reducing their costs and increasing plant lifespan. Moreover, it was not found in literature some computational tools of management scope that are able to assist in the identification, measurement, and analysis of these performance indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding medium and large PV systems, which use many components in different sizes and configurations, it is difficult to estimate trends for fault diagnosis. Santiago et al [18] developed a software to carry out a performance study of PV system components, using data recorded by inverters, providing access and visualization through color maps. Chine et al [19] proposed a method to determine the location of a failure in a PV plant by monitoring the ratio between DC and AC power.…”
Section: Introductionmentioning
confidence: 99%